2011
DOI: 10.1016/j.bios.2010.08.082
|View full text |Cite
|
Sign up to set email alerts
|

The importance of interfacial design for the sensitivity of a label-free electrochemical immuno-biosensor for small organic molecules

Abstract: An immuno-biosensing interface comprising a mixed layer of an oligo(ethylene glycol) (OEG) component, and an oligo(phenylethynylene) molecular wire (MW) is described. The OEG controls the interaction of proteins and electroactive interferences with the surface and the MW allows electrochemical communication to the underlying glassy carbon electrode. The layers are formed from in situ generated-aryl diazonium cations. To the distal end of the MW, a redox probe 1,1'-di(aminomethyl)ferrocene is attached followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…In consequence, this causes the changes in the permeability of counter ions to Cu(II) redox centers. The similar phenomenon was recently described by Gooding et al These authors showed, that antibody binding to the sensing interface causes a modulation of the ferrocene electrochemistry, due to restriction of counter ions accessing the redox probe to balance the charge [41]. …”
Section: Afm Characterization Of Nac/dp-cu(ii)-his 6 -Rage V Domain Sammentioning
confidence: 51%
“…In consequence, this causes the changes in the permeability of counter ions to Cu(II) redox centers. The similar phenomenon was recently described by Gooding et al These authors showed, that antibody binding to the sensing interface causes a modulation of the ferrocene electrochemistry, due to restriction of counter ions accessing the redox probe to balance the charge [41]. …”
Section: Afm Characterization Of Nac/dp-cu(ii)-his 6 -Rage V Domain Sammentioning
confidence: 51%
“…They discovered that the distance of ferrocene units from the electrode surface as well as the presence of different anions in the basic electrolyte strongly influence the voltammetric response of redox active monolayer. The alternation of ferrocene electrochemistry caused by antibody binding to the sensing redox active interface was described by Gooding et al [44]. The authors concluded the base of phenomenon observed was the restriction of counter ions accessing the redox sites to balance the charge.…”
Section: Resultsmentioning
confidence: 98%
“…Association or dissociation of the antibody at the sensing interface caused a modulation of the ferrocene electrochemistry, due to the restriction of counter ions access the redox probe (Khor et al, 2011).…”
Section: The Mechanism Of Response Of 3-iron Bis(dicarbollide)-oligonmentioning
confidence: 99%